Alleviation of Autophagic Deficits and Neuroinflammation by Histamine H3 Receptor Antagonist E159 Ameliorates Autism-Related Behaviors in BTBR Mice - Shilu Deepa Thomas; Petrilla Jayaprakash; Nurfirzana Z. H. J. Marwan; Ezzatul A. B. A. Aziz; Kamil Kuder; Dorota Łażewska; Katarzyna Kieć-Kononowicz; Bassem Sadek (MDPI AG, 2024)
Background/Objectives: Autism spectrum disorder (ASD) is a neurodevelopmental condition marked by social interaction difficulties, repetitive behaviors, and immune dysregulation with elevated pro-inflammatory markers. Autophagic deficiency also contributes to social behavior deficits in ASD. Histamine H3 receptor (H3R) antagonism is a potential treatment strategy for brain disorders with features overlapping ASD, such as schizophrenia and Alzheimer's disease. Methods: This study investigated the effects of sub-chronic systemic treatment with the H3R antagonist E159 on social deficits, repetitive behaviors, neuroinflammation, and autophagic disruption in male BTBR mice. Results: E159 (2.5, 5, and 10 mg/kg, i.p.) improved stereotypic repetitive behavior by reducing self-grooming time and enhancing spontaneous alternation in addition to attenuating social deficits. It also decreased pro-inflammatory cytokines in the cerebellum and hippocampus of treated BTBR mice. In BTBR mice, reduced expression of autophagy-related proteins LC3A/B and Beclin 1 was observed, which was elevated following treatment with E159, attenuating the disruption in autophagy. The co-administration with the H3R agonist MHA (10 mg/kg, i.p.) reversed these effects, highlighting the role of histaminergic neurotransmission in observed behavioral improvements. Conclusions: These preliminary findings suggest the therapeutic potential of H3R antagonists in targeting neuroinflammation and autophagic disruption to improve ASD-like behaviors.